INTERFAITH SOCIAL SOLIDARITY: A SOCIO-THEOLOGICAL ALTERNATIVE TO POST-PANDEMIC COMMUNITY EMPOWERMENT - Fitriatul Hasanah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
The welfare of citizens, particularly in Sukoreno Village, Jember, East Java, has been adversely affected by the Covid-19 pandemic in Indonesia over the past 2 (two) years. Efforts based on socio-theological principles and interfaith civil society have emerged as alternative solutions to address this issue. The purpose of this article is to elucidate the manifestations of interfaith social solidarity in Sukoreno Village, Jember, East Java, as a means of overcoming the economic challenges faced by the community in the post-Covid-19 pandemic. This study employed a qualitative method. Data collection techniques are carried out through observation, in-depth interviews, and document review. The findings indicated that this form of interfaith solidarity was fostered through the utilization of social capital within the community. Examples of such solidarity include social services, heightened Covid-19 awareness, and the optimization of micro, small, and medium enterprises (MSMEs) and local village resources. While these efforts may not directly lead to significant improvements in the economic welfare of the community, they do highlight that community empowerment can be achieved through an interfaith approach.Pandemi Covid-19 di Indonesia selama 2 (dua) tahun terakhir telah menurunkan tingkat kesejahteraan warga, khususnya di Desa Sukoreno, Jember, Jawa Timur. Upaya berbasis sosio-teologi masyarakat sipil lintas agama menjadi salah satu alternatif dalam mengatasi problem tersebut. Artikel ini bermaksud untuk menjelaskan bentuk-bentuk solidaritas sosial lintas agama di Desa Sukoreno, Jember, Jawa Timur dalam mengatasi problem ekonomi masyarakat pasca pandemi. Penelitian ini menggunakan metode kualitatif. Teknik pengumpulan data dilakukan melalui observasi, wawancara mendalam, dan telaah dokumen. Hasil penelitian mengungkapkan bahwa bentuk solidaritas lintas agama ini muncul melalui pemanfaatan modal sosial yang ada di masyarakat. Diantaranya dalam bentuk bakti sosial, sigap Covid-19, dan optimalisasi UMKM dan potensi lokal desa. Upaya ini meskipun tidak dapat menjustifikasi peningkatan kesejahteraaan ekonomi warga, namun dapat merefleksikan bahwa pemberdayaan masyarakat dapat dilakukan dengan pendekatan lintas agama.